Perancangan Aplikasi Bahasa Daerah Tontemboan Berbasis Website - Tirsa Julianti Saruan; Arnold Horalto Umboh (Jurusan Teknik Elektro Fakultas Teknik Universitas Halu Oleo, 2023)
Every region in Indonesia has its regional language, which is called the mother tongue, this language is used as a medium of communication. A regional language is a traditional language in an area which has been inherited from generation to generation by the speaking community where the language is spoken. The totemboan language itself is a cultural asset in the South Minahasa region. At present the use of regional languages, especially the tontemboan regional language among the younger generation is decreasing day by day. The younger generation prefers to keep up with the latest developments rather than using the totemboan regional language. Observation results show a decrease in regional language users, those who use the Tontemboan regional language are parents aged 50 years and over, based on this, the Tontemboan regional language is threatened with extinction. The aim of this research is to develop a website-based Tontemboan regional language application to increase cultural literacy knowledge in South Minahasa district